Disoriented collagen fibers and disorganized, fibrotic orbicularis oris muscle fiber with mitochondrial myopathy in non-syndromic cleft lip. (August 2022) - Noor, Rabiatul Adawiyah Mohamad; Shah, Nurul Syazana Mohamad; Zin, Anani Aila Mat; Sulaiman, Wan Azman Wan; Halim, Ahmad Sukari
Abstract: Objective: This study aims to explore and compare the histopathology of upper cleft lip tissue in order to identify the abnormalities and orientation of muscle and collagen fibers in patients affected with non-syndromic cleft lip with or without cleft palate (NSCL±P) and normal controls. Materials and methods: Eight fresh lip tissues of consented patients with NSCL±P and two controls were fixed and stained with hematoxylin and eosin (H&E), Masson's trichrome (MT), and modified Gomori trichrome techniques. The images were captured and examined using imaging cellSens software (Olympus, Tokyo, Japan) and Mirax Scan (Carl Zeiss, Germany). The H&E stained tissues were analysed for muscle fiber size using image processing program (imageJ, USA). Histopathological appearance of epidermal and dermal layers including collagen orientation, as well as muscle fibers abnormalities were observed. Results: Tissues stained with H&E exhibit pseudoepitheliomatous hyperplasia, epidermal and sebaceous glands hyperplasia. Morphometric analysis of muscle fibers showed the diameter was between 6.912 and 10.246 µm. Collagen fibers were densely packed in cleft tissue, but muscle fibers were sparse in MT stain. Modified Gomori trichrome stain revealed hypoplastic muscle with fibrosis, including ragged red fibers. Conclusion: Disoriented collagen fibers, significant sparse and disorganized orbicularis oris muscle fibers with classical myopathic appearances proved that cleft tissue had abnormal histology findings. These findings further support the mechanism of collagen and muscle fibers during embryonic development that causing cleft formation. Highlights: Histological pattern of epithelium and collagen fibers in lip skin. Histopathology of orbicularis oris muscle in patients with NSCL±P. The association of mitochondrial myopathy in patients with NSCL±P.